A Novel Approach for COVID-19 Patient Condition Tracking: From Instant Prediction to Regular Monitoring - Bakin, Evgeny A.; Stanevich, Oksana V.; Chmelevsky, Mikhail P.; Belash, Vasily A.; Belash, Anastasia A.; Savateeva, Galina A.; Bokinova, Veronika A.; Arsentieva, Natalia A.; Sayenko, Ludmila F.; Korobenkov, Evgeny A.; Lioznov, Dmitry A.; Totolian, Areg A.; et al. (Frontiers in Medicine, 2021)
Purpose. The aim of this research is to develop an accurate and interpretable aggregated score not only for hospitalization outcome prediction (death/discharge) but also for the daily assessment of the COVID-19 patient's condition. Patients and methods. In this single-center cohort study, real-world data collected within the first two waves of the COVID-19 pandemic were used (collected 27.04.2020-03.08.2020 and 01.11.2020-19.01.2021 respectively). The first wave data (1349 cases) was used as a training set for the score development, while the second wave data (1453 cases) was used as a validation set. No overlapping cases presented in the study. For all the available patients' features, we tested their association with an outcome. Significant features were taken for further analysis, and their partial sensitivity, specificity, and promptness were estimated. Sensitivity and specificity were further combined into a feature informativeness index. The developed score was derived as a weighted sum of nine features that showed the best trade-off between informativeness and promptness. Results. Based on the training cohort (median age 58±13.3, females 55.7%, males 44.3%) the following resulting score was derived: APTT (4 points), CRP (3 points), D-dimer (4 points), glucose (4 points), hemoglobin (3 points), lymphocytes (3 poq1eints), total protein (6 points), urea (5 points), and WBC (4 points). Internal and temporal validation based on the second wave cohort (median age 60±14.8, females 51.8%, males 48.2%) showed that a sensitivity and a specificity over 90% may be achieved with an expected prediction range >7 days. Moreover, we demonstrated high robustness of the score to the varying peculiarities of the pandemic. Conclusions. An extensive application of the score during pandemic showed its potential for the optimization of patient management as well as improvement of medical staff attentiveness in a high workload stress. The transparent structure of the score, as well as tractable cutoff bounds, simplified its implementation into clinical practice. The high cumulative informativeness of the nine score components suggests that these are the indicators that need to be monitored regularly during the follow-up of a patient with COVID-19.